Breast Cancer: Recent Progress - Olivotto, Ivo (Operating Room Nurses Association of Canada Journal, 1992)
Breast cancer is the commonest malignancy affecting Canadian women. One in ten women will develop breast cancer sometime in her life. Nearly 15,000 new cases will be diagnosed and over 5,000 women will die of breast cancer in Canada in 1992. These statistics are frightening. There are three ways to reduce morbidity and mortality from breast cancer; prevention, screening and better treatment. This article will review progress which has been made in the past ten years in all three areas.